Canada : Financial Sector Assessment Program-Insurance Core Principles-Detailed Assessment of Observance. (IMF Staff Country Reports; Country Report ;, 2014)
This Detailed Assessment report, a part of the 2013 Financial Sector Assessment Program (FSAP) of Canada, assesses Canada's regulatory regime and supervisory practices against the international standards. The IMF report suggests that the Office of the Superintendent of Financial Institutions (OSFI) should be empowered to take supervisory measures at the level of the holding company. It highlights that while OSFI requires Federally Regulated Insurers (FRI) FRIs to develop internal capital targets, requirements to develop an Own Risk and Solvency Assessment are scheduled to be implemented in 2014.